2007
DOI: 10.1016/j.bbr.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Activation in extended amygdala corresponds to altered hedonic processing during protracted morphine withdrawal

Abstract: Previously we reported that during protracted morphine abstinence rats show reduced conditioned place preferences (CPP) for food-associated environments, compared to non-dependent subjects. To determine the brain regions involved in this altered reward behavior, we examined neural activation (as indexed by Fos-like proteins) induced by a preference test for a food-associated environment in five-week morphine-abstinent vs non-dependent animals. The results indicate that elevated Fos expression in the anterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 54 publications
(74 reference statements)
3
52
1
3
Order By: Relevance
“…How this might have translated into enhanced avoidance of the center region is unclear. Clues to a mechanism, however, derive from studies investigating the neural basis of increased negative affect associated with opiate withdrawal (Delfs et al, 2000;Harris and Aston-Jones, 2007). These studies have indicated a critical role of the BST, and in particular, its catecholaminergic inputs from the caudal brainstem.…”
Section: Patterns Of Neuronal Activation Following the Open Field/holmentioning
confidence: 99%
See 1 more Smart Citation
“…How this might have translated into enhanced avoidance of the center region is unclear. Clues to a mechanism, however, derive from studies investigating the neural basis of increased negative affect associated with opiate withdrawal (Delfs et al, 2000;Harris and Aston-Jones, 2007). These studies have indicated a critical role of the BST, and in particular, its catecholaminergic inputs from the caudal brainstem.…”
Section: Patterns Of Neuronal Activation Following the Open Field/holmentioning
confidence: 99%
“…These studies have indicated a critical role of the BST, and in particular, its catecholaminergic inputs from the caudal brainstem. Blockade of adrenergic receptors in the BST prevented development of place aversions in rats undergoing morphine withdrawal (Harris and Aston-Jones, 2007). Like morphine withdrawal, immune challenge with lipopolysaccharide (a component of gramnegative bacterial cell walls) activates caudal brainstem projection neurons (A1/C1 cell group in the VLM and the A2/C2 cell group in the NTS) that target the BST directly (Gaykema et al, 2007).…”
Section: Patterns Of Neuronal Activation Following the Open Field/holmentioning
confidence: 99%
“…1) (Zahm et al 2011). Evidence suggests that activity within the CeA and BNST during protracted withdrawal may produce a "stress-like" state that can precipitate relapse (Nakagawa et al 2005b;Harris and Aston-Jones 2007). Indeed, for cocaine, these regions are only critical for reinstatement triggered by stress (McFarland et al 2004).…”
Section: Amygdala Outputsmentioning
confidence: 99%
“…Increased morphine preference and decreased food preference in protracted abstinence animals have been associated with increased Fos activation in stress-related brain areas, such as extended amygdala and nucleus tractus solitarius (Harris and AstonJones, 2003a;Harris and Aston-Jones, 2007a). In addition, previous exposure to stress has been shown to increase the subsequent acquisition of morphine place preference, an effect that is attenuated by corticosterone inhibition during CPP acquisition, but not during stress exposure (DerAvakian et al, 2005;Will et al, 1998).…”
Section: Discussionmentioning
confidence: 99%